THE FAIR VALUE OF DEFERRED REVENUE - Valentin Gabriel CRISTEA (Challenges of the Knowledge Society)
Deferred income has been recognized by the acquiring entity or by the acquirer on their balance prior to the combination. During the deal, deferred revenue must be recorded at fair value according to GAAP . The amount of these deferred income liabilities should be reflected in the financial statements. Recommendations on this topic are covered in the FASB Coding Accounting Standard (AUC) Topic 805, Business Combinations. This rule eliminates some book-tax timing differences regarding unearned revenue, also known as deferred revenue. It is known that the Financial Accounting Standards (SFAS) 141 (R), Business Combinations, was issued in December 2007, in force for the annual reporting periods from 15 December 2008. Since then, paragraph 20 of SFAS 141 (R) (AUC 805- 20-30-1) requires that “the acquirer must measure the identifiable assets acquired, the assumed liabilities and any uncontrolled interest in the entity acquired at fair value at the date of acquisition". The guidelinesimpose two facts: estimating the fair value at the time of acquisition and recognizing liability when the obligation to perform exists. These deferred income debts that were recognized by the acquired entity or by the acquirer on their precombination balance sheets do not appear as deferred income liabilities in the post-business period of the acquirer combined financial statements. Performance obligations and fair market values affect the value of deferred income debts that an acquirer would recognize in post-business combination accounting. Thus, the combined income from the post-business combination of companies is significantly lower than total revenue between the two companies if they didn't have been merged. Moreover, the rights regained it doesn't just interact with the deferred amount income liabilities and income during the period postcombination business period, but influences revenue through additional expenses or income.